Dampak Indeks Ketidakpastian Kebijakan Moneter dan Nilai Tukar Terhadap IHSG Indonesia - I Made Hegar Danendra Nararya; Daffa Sukma Falih; Farhan Taufiqurrahman; Ladi Wajuba Perdini Fisabilillah; Dita Dismalasari Dewi (Independent: Journal of Economics, 2025)
This study aims to analyze the impact of the Monetary Policy Uncertainty (MPU) index and exchange rates on the Jakarta Composite Index (IHSG) in Indonesia from January 2018 to December 2023. The method used is the Vector Error Correction Model (VECM), with data sourced from the Federal Reserve Economic Data (FRED). The analysis results show that both exchange rates and the MPU index have a significant negative relationship with the IHSG, where depreciation of the exchange rate and high MPU will weaken the IHSG in the long term. Additionally, the response of the IHSG to shocks in exchange rates and MPU indicates a positive direction, suggesting that the Indonesian stock market shows resilience to these shocks. This research is expected to provide new insights for policymakers in formulating strategies to address the impacts of economic uncertainty.